PM2.5 pollution in Texas: a geospatial analysis of health impact functions - Bryan, Luke; Landrigan, Philip (Frontiers in Public Health, 2023)
Background Air pollution is the greatest environmental threat to human health in the world today and is responsible for an estimated 7–9 million deaths annually. One of the most damaging air pollutants is PM2.5 pollution, fine airborne particulate matter under 2.5 microns in diameter. Exposure to PM2.5 pollution can cause premature death, heart disease, lung cancer, stroke, diabetes, asthma, low birthweight, and IQ loss. To avoid these adverse health effects, the WHO recommends that PM2.5 levels not exceed 5 μg/m3. Methods This study estimates the negative health impacts of PM2.5 pollution in Texas in 2016. Local exposure estimates were calculated at the census tract level using the EPA’s BenMAP-CE software. In BenMAP, a variety of exposure-response functions combine air pollution exposure data with population data and county-level disease and death data to estimate the number of health effects attributable to PM2.5 pollution for each census tract. The health effects investigated were mortality, low birthweight, stroke, new onset asthma, new onset Alzheimer’s, and non-fatal lung cancer. Findings This study found that approximately 26.7 million (98.9%) of the 27.0 million people living in Texas in 2016 resided in areas where PM2.5 concentrations were above the WHO recommendation of 5 μg/m3, and that 2.6 million people (9.8%) lived in areas where the average PM2.5 concentration exceeded 10 μg/m3. This study estimates that there were 8,405 (confidence interval [CI], 5,674–11,033) premature deaths due to PM2.5 pollution in Texas in 2016, comprising 4.3% of all deaths. Statewide increases in air-pollution-related morbidity and mortality were seen for stroke (2,209 – CI: [576, 3,776]), low birthweight (2,841 – CI: [1,696, 3,925]), non-fatal lung cancers (636 – CI: [219, 980]), new onset Alzheimer’s disease (24,575 – CI: [20,800, 27,540]), and new onset asthma (7,823 – CI: [7,557, 8,079]). Conclusion This study found that air pollution poses significant risks to the health of Texans, despite the fact that pollution levels across most of the state comply with the EPA standard for PM2.5 pollution of 12 μg/m3. Improving air quality in Texas could save thousands of lives from disease, disability, and premature death.